Storage Projects in Nepal’s Electricity Development Decade 2016/2026 For Whom Nepal’s Storage Projects Toll? - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
The Nepal government’s Electricity Development Decade 2016/2026 to develop 10,000 MW in 10 years has 11 storage projects totaling over 5,000 MW. Nine of these eleven projects would store 11 billion cubic meters of freshwater submerging vast tracts of fertile valleys, villages, farms and forests in Nepal. Brushing aside these social and environmental costs lightly, the government has launched the holy ‘jihad/crusade’ to develop hydroelectricity. Nepal’s policy framers of 10,000 MW in 10 years crusade have totally failed to see the larger picture in the Ganges basin. This failure to see the larger Ganges picture is, to a large extent, attributed to Prime Minister Madhav Kumar Nepal’s 2009 decision to unbundle Water Resources Ministry into Energy and Irrigation. Electricity attained the upper class status with Water downgraded to Dalit class!India’s greatest burning problem in the Ganges basin, that supports nearly fifty per cent of her 1,200 million people, is WATER. India, therefore, is in desperate need of storages in Nepal to realize her master plan, the Interlinking of Rivers. With Nepal in desperate pursuit of hydroelectricity, India sees this as an opportune moment to avail GRATIS stored WATER through Nepal’s default. According to Bhim Subba, a Bhutanese of Nepalese origin, this is the fundamental flaw in all past Indo-Nepal deals. Subba believes India must concede that success of her Ganges water strategy hinges entirely on Nepal. He argues that water stored in Nepal has monetary value and this must be factored in all storage projects. Such a policy would be mutually beneficial for both the countries. Unfortunately, this would be a bitter pill to swallow for our policy framers of 10,000 MW in 10 years crusade. This article dwells on these issues. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 20Page: 6-10